Analisis Kepuasan Pelanggan mengenai Kualitas Pelayanan Astra Motor Slawi di Kabupaten Tegal (Universitas Negeri Semarang, 2015)
This study aims to describe and analyze the dimensions of responsiveness, reliability, empathy, assurance and physical evidence on the quality of services determine customer satisfaction. The sample in this study amounted to 100 customers. The sampling technique using non-probability sampling with accidental sampling technique. The variables of this study consisted of customer satisfaction and service quality. Analysis of the data used is descriptive analysis. The results showed five dimensions of service quality, the dimensions of responsiveness, reliability, empathy and assurance shows that customers are very satisfied, and to the dimensions of the physical evidence indicates that the customer is not satisfied. This research is expected as input for Astra Motor Slawi Tegal to increase the dimensions of the performance of the physical evidence on the quality of service by providing adequate facilities and infrastructure. Besides the leader is more attention is needed for the arrangement of items in the showroom, interior space and provide the missing clues for each room allowing customers find the space needed.